Intra-cycle velocity variations, swimming economy, performance, and training in swimming - Vilas-Boas, J. P.; Fernandes, R. J.; Barbosa, T. M. (World book of swimming: From science to performance, 2012)
This chapter deals with intra-cyclic velocity variations within a swimming stroke cycle (dv), and its variation with technique, exercise intensity, energy expenditure and fatigue, as a relevant parameter to assess biomechanical and coordinative development of swimming technique. The text starts through the theoretical foundations of the assumption, relating variable movement with increased energy demands and biomechanical proficiency. Then it progresses to the definition of the actual state of the art of the practical solutions available for its assessment, with special emphasis on the discussion about the convenience of centre of mass or a fixed anatomical point assessment. The relationships between dv and other performance related/determinant factors, both biomechanical and coordinative or physiologic and energetic, will be also addressed. Finally, the chapter concludes with considerations related to the applications of the study of dv to performance and training evaluation and advice.